Exports and the economic performance of large state-owned enterprises in Poland: evidence from firm-level data - Szarzec, Katarzyna; Nowara, Wanda; Olejnik, Iwona (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
The aim of this paper is to investigate the relation between exports and economic performance, and the extent of state ownership in the largest non-financial enterprises in Poland in 2011–2015. We address the following research questions: (i) What is the share of export companies in the group of the largest non-financial enterprises in Poland in terms of ownership structure (stateowned and privately-owned companies) and sectors? (ii) Are there differences in the economic performance of exporting companies compared to their non-exporting counterparts? Among the largest exporters, state-owned companies and companies from the manufacturing and mining sectors still dominate. Exporting state-owned enterprises have higher productivity than non-exporters, which could be caused by their dominant position on the domestic oligopolistic market. Exporting private-owned companies performed better in the case of ROA and ROE than exporting SOEs. This could be explained by the fact that private companies have a higher efficiency of property management and are expected to pay dividends by their shareholders.